PENYEBARAN NARKOTIKA DI WILAYAH HUKUM SEMARANG BARAT DALAM PERSPEKTIF KRIMINOLOGI - Nanda Rizky Setyowati (Jurnal Ilmiah Dinamika Hukum, 2021)
The spread of narcotics in Semarang City in 2019-2020 is possible to increase, especially in the West Semarang area. It was proven that in 2017 it was revealed 198 cases then in 2018 it became 287 cases. The author is interested in examining the factors that influence the spread of narcotics in the West Semarang area and the public reaction to the spread of narcotics in the West Semarang area. Research in this writing uses Sociological Juridical type with descriptive-analytical research specifications through primary and secondary data sources. Based on the results of the study, the factors that influence the spread of narcotics in the West Semarang area can be divided into two major factors, namely internal factors and external factors which can be analyzed using the analysis of Criminal Sociology Theory such as Ecological Theory, Cultural Conflict Theory, Economic Theory, Differential Association Theory. ), and Anomic Theory, while the public reaction regarding the distribution of narcotics can be seen from two views, namely from the community and law enforcement officials. Keywords : Criminological Theory; Spread; Narcotics.